Flavonoids of Memecylon umbellatum (Burm.) - Joshi, Himanshu; B. Joshi, Arun.; Gururaj, M.P.; Sati, Hemlata (Asian Journal of Chemistry, 2010)
The flavonoids quercetin, rutin and apigenin has been isolated from the roots of Memecylon umbellatum and their structure were established by spectral analysis and direct comparison with authentic samples.